Flavonoids with Anti-Herpes Simplex Virus Properties: Deciphering Their Mechanisms in Disrupting the Viral Life Cycle - Šudomová, Miroslava; Hassan, Sherif T S (Viruses, 2023)
The herpes simplex virus (HSV) is a double-stranded DNA human virus that causes persistent infections with recurrent outbreaks. HSV exists in two forms: HSV-1, responsible for oral herpes, and HSV-2, primarily causing genital herpes. Both types can lead to significant complications, including neurological issues. Conventional treatment, involving acyclovir and its derivatives, faces challenges due to drug resistance. This underscores the imperative for continual research and development of new drugs, with a particular emphasis on exploring the potential of natural antivirals. Flavonoids have demonstrated promise in combating various viruses, including those within the herpesvirus family. This review, delving into recent studies, reveals the intricate mechanisms by which flavonoids decode their antiviral capabilities against HSV. By disrupting key stages of the viral life cycle, such as attachment to host cells, entry, DNA replication, latency, and reactivation, flavonoids emerge as formidable contenders in the ongoing battle against HSV infections.
Keywords: natural products; Antiviral Agents; HSV life cycle; lidé; Herpesvirus 1, Human; herpes simplex virus; Herpes Simplex; flavonoids; HSV-2; Humans; stadia vývoje; lidský herpesvirus 1; host–virus interaction; flavonoidy; Life Cycle Stages; natural antivirals; antivirové látky; zvířata; drug resistance; antiviral properties; cellular pathways; Animals; herpes simplex; Flavonoids; HSV-1